2021
DOI: 10.3389/fendo.2021.654473
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as Targets of Novel Therapies for Graves’ Ophthalmopathy

Abstract: Graves’ disease (GD) is an organ-specific autoimmune disorder of the thyroid, which is characterized by circulating TSH-receptor (TSH-R) stimulating antibodies (TSAb), leading to hyperthyroidism. Graves’ ophthalmopathy (GO) is one of GD extra-thyroidal manifestations associated with the presence of TSAb, and insulin-like growth factor-1 receptor (IGF-1R) autoantibodies, that interact with orbital fibroblasts. Cytokines are elevated in autoimmune (i.e., IL-18, IL-6) and non-autoimmune hyperthyroidism (i.e., TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 92 publications
(105 reference statements)
0
22
0
Order By: Relevance
“…Tocilizumab, a humanized recombinant IL-6R monoclonal antibody, can improve disease activity and severity in corticosteroid-resistant GO patients ( Perez-Moreiras et al., 2018 ; Sánchez-Bilbao et al., 2020 ). Infliximab, an antitumor necrosis factor (TNF)-α antibody, has been successfully used to treat sight-threatening GO ( Durrani et al., 2005 ; Komorowski et al., 2007 ; Fallahi et al., 2021 ). Both IL-6 and TNF-α are monocyte-derived key proinflammation cytokines.…”
Section: The Effects On the Gut Microbiota Of Therapeutic Agents For Gd/gomentioning
confidence: 99%
“…Tocilizumab, a humanized recombinant IL-6R monoclonal antibody, can improve disease activity and severity in corticosteroid-resistant GO patients ( Perez-Moreiras et al., 2018 ; Sánchez-Bilbao et al., 2020 ). Infliximab, an antitumor necrosis factor (TNF)-α antibody, has been successfully used to treat sight-threatening GO ( Durrani et al., 2005 ; Komorowski et al., 2007 ; Fallahi et al., 2021 ). Both IL-6 and TNF-α are monocyte-derived key proinflammation cytokines.…”
Section: The Effects On the Gut Microbiota Of Therapeutic Agents For Gd/gomentioning
confidence: 99%
“…A number of immune cells and cytokines are thought to be involved in the pathogenesis of TED ( 43 , 44 ). Several monoclonal antibodies able to interfere with cytokine signalling are available for treatment of moderate-to-severe TED, but only a few of these immunosuppressants have been tested in randomized clinical trials.…”
Section: Systemic Medical Therapymentioning
confidence: 99%
“…Zheng et al 10.3389/fimmu.2022.952954 be hypothesized that cell-mediated (Th1-type) immune responses predominate in the early phases of GO, whereas humoral immunity (Th2-type) plays a larger role in the latter stages.Th1 cells produce cytokines including interferon (IFN)-g, interleukin (IL)-1, IL-2, and tumor necrosis factor (TNF)-a, which cause OFs to create and release significant amounts of glycosaminoglycans like hydrophilic hyaluronan, resulting in swelling of orbital tissues (especially the extraocular muscles) (8). Among others, it has also been shown that IL-1b is associated with adipogenesis in GO (9).…”
Section: Immune Factors 21 Cellular Immunitymentioning
confidence: 99%